Identification of a reverse crossover point during moderate-intensity exercise (>6 h; 69% VO2max) in a world-class triathlete—A secondary analysis - Noakes, Timothy; Buga, Alex; Volek, Jeff; Prins, Philip (Frontiers in Nutrition, 2025)
Graphical abstractRe-analysis results (Left) and takeaway messages (Right) are summarized above. RCOP, reverse crossover point. Figure created with Biorender.com.Reverse Crossover Point (RCOP) analysis showing a man on an exercise bike and running, indicating training intensity. A graph illustrates substrate oxidation levels over time, with fat oxidation surpassing carbohydrate oxidation. Key takeaways: Fat oxidation increased significantly despite carbohydrate intake, suggesting additional carbohydrate sources and reliance on lipids for energy.